Tailoring the linear and nonlinear optical properties of NiO thin films through Cr3+ doping - Shkir, Mohd; Ganesh, V.; AlFaify, S.; Yahia, I. S.; Zahran, H. Y. (Journal of materials science. Materials in electronics, 2018)
NiO is an excellent contender for smart windows, electrochemical super capacitor and dye sensitized photocathode. Hence, thin films of NiO with different concentrations (1, 3, 5 and 7 wt%) of Cr doping has been fabricated by a facile and low cost technique. The analysis of effect of Cr concentrations on structural, vibrational, morphological, optical and nonlinear optical properties has been studied. X-ray diffraction study confirms that the fabricated films are of polycrystalline nature with cubic phase. The determination of structural parameters such as crystallite size, dislocation density, lattice strain and number of crystallites per unit area was done. The presence of Cr doping in NiO was confirmed by EDX analysis. The vibrational modes were studied by FT-Raman analysis. AFM topography was recorded for pure and Cr doped NiO films. The crystallite/grain size was found to be in the range of 36–40 nm (from X-ray) and 6–12 nm (from AFM). High optical transparency was observed from visible to near infrared region for all the deposited films which is ~ 70 to 85%. The direct and indirect optical band gap were calculated and the direct band gap is found in the range of 3.85–3.78 eV. The optical constants like linear and nonlinear refractive index ( n 2 ) , optical dielectric constant and loss, optical and electrical conductivity, third order nonlinear optical susceptibility ( χ 3 ) were calculated from reflectance and absorbance data. The values of n 2 and χ 3 are found to be of order of 10 −7 and 10 −9 esu, respectively.